(untitled) (Eurasian Scientific Herald, 2022)
This article discusses the role of integration in the training of future English teachers, in particular, the benefits of integrating foreign languages with other disciplines, research on integrated language learning illuminates them in detail. The role of integration is very important in preparing future foreign language teachers to teach students. Based on the integration of future foreign language teachers into teaching, preparing students for teaching, not only the expected and unexpected results in the acquisition and acquisition of knowledge by the student, but also in improving the ability and skills of the teacher can be achieved. In addition, the integration of lessons and the training of teachers based on integration, preparation for lessons is one of the most pressing issues of our time.